Effect of long-term transcutaneous auricular vagus nerve stimulation in multiple system atrophy-cerebellar subtype: a case report - Wang, Zhao-Di; Cheng, Xiao-Ping; Liu, Zhen-Yi; Wu, Di; Ni, Jun; Chen, Chuan-Juan; Chen, Xin-Yuan (Frontiers in Neuroscience, 2025)
BackgroundMultiple system atrophy-cerebellar subtype (MSA-C) is a predominance of cerebellar ataxia and autonomic failure. MSA-C has a rapid progression, with average 9 years from symptom onset to death. Despite its prevalence, there is still a lack of effective treatments. In recent years, it has been established that taVNS has significant therapeutic effects on epilepsy, depression, migraine, insomnia, and other diseases. Hence, we performed taVNS treatment for one MSA-C patient to explore whether taVNS could alleviate patient’s motor and non-motor symptoms.Case presentationA 65-year-old woman diagnosed with MSA-C received taVNS treatment for the following duration and course: once a day, 40 min a time, 20 times a month continually for 12 months. Meanwhile, she received assessments of motor and non-motor symptoms at baseline, 4-weeks and 12-months after taVNS treatment. Motor symptoms assessments was made by Scale for the Assessment and Rating of Ataxia (SARA) and Unified Multiple System Atrophy Rating Scale (UMSARS), non-motor symptoms assessment by Pittsburgh Sleep Quality Index (PSQI), Hamilton Anxiety Scale (HAMA), and Hamilton Depression Scale (HAMD). After 4-weeks and 12-months of taVNS treatment, compared to baseline assessments, SARA scores decreased from 13 to 11 and then to 10.5, UMSARS scores from 28 to 24 and then to 23, PSQI scores from 19 to 13 and then to 6, HAMA scores from 13 to 3 and then remained unchanged, and HAMD scores from 7 to 4 and then remained unchanged.ConclusionIn the case, we found that short-term taVNS treatment can alleviate ataxia, sleep problem, anxiety and depression of the MSA-C patient. The effects can be maintained and some symptoms may be further improved after receiving long-term treatment. Our case report supports the feasibility and effectiveness of taVNS treatment in MSA-C patients.